ST6Gal1: Oncogenic signaling pathways and targets - GC, Sajina; Bellis, Susan L.; Hjelmeland, Anita B. (Frontiers in Molecular Biosciences, 2022)
The Golgi-sialyltransferase ST6Gal1 (βgalactosidase α2,6 sialyltransferase 1), adds the negatively charged sugar, sialic acid, to the terminal galactose of N-glycosylated proteins. Upregulation of ST6Gal1 is observed in many malignancies, and a large body of research has substantiated that ST6Gal1-mediated 2,6 sialylation impacts cancer hallmarks. ST6Gal1 affects oncogenic behaviors including sustained proliferation, enhanced self-renewal, epithelial-to-mesenchymal transition, invasion, and chemoresistance. However, there are relatively few ST6GaL1 related signaling pathways that are well-established to mediate these biologies. Additionally, greater delineation of specific targets and signaling mechanisms that are orchestrated by ST6Gal1 is needed. The aim of this review is to provide a comprehensive summary of our current understanding of select oncogenic signaling pathways and targets affected by ST6Gal1.